From E-learning to Blended Learning: Re-designing Content and Frame in a Capacity Building Project - Hansen, Line Skov; Hansen, Ole (International Journal of Emerging Technologies in Learning (iJET), 2013)
This paper presents the didactical considerations, theoretical approaches and first experiences with a cohesive school and kindergarten research-based development project in a Norwegian municipality. The project involves 41 schools and 70 kindergartens, inclusive all leaders and pedagogical staff. The project uses a â??capacity buildingâ? strategy where new practice and skills are built through pedagogical interventions mostly designed as courses based on blended learning with a dialogue oriented and practice related team-work as an important part. Through this work the team learns how to use a specific model for pedagogical analysis. By this model the team gets the opportunity to contribute and to collaborate on tasks related to their own practice. From our experience and from the qualitative research in a similar project in Denmark, with more than 500 schools and 29400 teachers, we know that these teams and thereby also the team facilitator play a very important role in the implementation of the new ideas and practices. Research from the Danish project also shows that both the content and frame in especially the course for team facilitators need a re-design.